1992
DOI: 10.1172/jci115555
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of aldosterone-induced increases in Cai2+ and Isc suggest that Cai2+ is the second messenger for stimulation of apical membrane conductance.

Abstract: Studies were performed on monolayers of cultured A6 cells, grown on permeable filters, to determine the second messenger system involved in the aldosterone-induced increase in electrogenic sodium transport. Addition of aldosterone (1 p&M Invest. 1992. 89:150-156.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 37 publications
5
9
0
Order By: Relevance
“…The present data indicate that the baseline [Ca 2ϩ ] i was 103 Ϯ 2 nM (n ϭ 58), and the stimulatory effect of aldosterone on the H ϩ -ATPase is associated with an increase in [Ca 2ϩ ] i , similar to that observed with angiotensin II (35) and arginine vasopressin (7,24). These results are also in accordance with several authors who found an aldosterone-induced increase in [Ca 2ϩ ] i (10,14,17,19,26,37), indicating that intracellular calcium is a prerequisite for aldosterone action. The increase in [Ca 2ϩ ] i might initiate events that lead to activation of H ϩ -ATPase (16), and the cell acidification stimulates a calciummediated exocytotic insertion of proton pumps, a process important for pH i regulation (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present data indicate that the baseline [Ca 2ϩ ] i was 103 Ϯ 2 nM (n ϭ 58), and the stimulatory effect of aldosterone on the H ϩ -ATPase is associated with an increase in [Ca 2ϩ ] i , similar to that observed with angiotensin II (35) and arginine vasopressin (7,24). These results are also in accordance with several authors who found an aldosterone-induced increase in [Ca 2ϩ ] i (10,14,17,19,26,37), indicating that intracellular calcium is a prerequisite for aldosterone action. The increase in [Ca 2ϩ ] i might initiate events that lead to activation of H ϩ -ATPase (16), and the cell acidification stimulates a calciummediated exocytotic insertion of proton pumps, a process important for pH i regulation (34).…”
Section: Discussionsupporting
confidence: 92%
“…The increase in [Ca 2ϩ ] i might initiate events that lead to activation of H ϩ -ATPase (16), and the cell acidification stimulates a calciummediated exocytotic insertion of proton pumps, a process important for pH i regulation (34). Our results with RU 486 also confirm this behavior since 1) this GR antagonist alone caused a significant decrease in the pHirr and in [ (26). However, the effect of a long-term increase in [Ca 2ϩ ]i is still not adequately explained.…”
Section: Discussionsupporting
confidence: 79%
“…6 and 7). This could be due to an unspecific inhibitory action of this GR antagonist, but it might also indicate that, in basal conditions, a basal level of aldosterone or some glucocorticoid binding to GR receptors may exist, causing some tonic activation of the Na (11,14,17,19,31,39), indicating that [Ca 2ϩ ] i is a prerequisite for aldosterone action. Nongenomic and pregenomic actions usually involve second messengers, such as inorganic ions, cAMP, or various protein kinases.…”
Section: Discussionmentioning
confidence: 99%
“…A high-affinity site, which is tonically inhibitory, binds to low Ca 2ϩ /calmodulin, thus suppressing the inhibition, that is, stimulating the exchanger at low Ca 2ϩ / calmodulin levels. A low-affinity site, however, binds with calcium and calmodulin only at high concentrations, and under these conditions inhibits the exchanger activity (26,28,38 (31). However, the effect of a long-term increase in [Ca 2ϩ ] i is still not adequately explained.…”
Section: Discussionmentioning
confidence: 99%
“…The role of intracellular Ca2+ ([Ca 2 +];) in regulating amiloride-sensitive epithelial Na+ channels is unclear. In renal epithelia, raising [Ca 2 +]; inhibits apical Na+ channels in rat cortical collecting tubule (Palmer & Frindt, 1987), whereas an early rise in [Ca2+] l governs the increase in apical Na+ channel activity stimulated by aldosterone in A6 renal cells (Petzel et al 1992). We therefore used the dual electrode voltage-clamp technique to assess the effect of raising [Ca2+]l on amiloride-sensitive whole-cell Na+ currents (I~;:-'il) in Xenopus oocytes expressing human renal Na+ channels.…”
mentioning
confidence: 99%